Implementasi Desain Gamifikasi Pada Pembelajaran Tajwid Dan Gharib Dengan Pendekatan Player Centered Design - Pratama, Muhammad Hisyam; Dwi Rolliawati; Khalid, Khalid (Systemic: Information System and Informatics Journal, 2025)
The Quran is the holy book that serves as a guide for Muslims. It is recommended to read the Quran fluently to avoid errors and adhere to the rules of tajweed and gharib. Conventional learning methods are often insufficient for mastering the Quran due to the challenging pronunciation of Hijaiyah letters and the Arabic language. Thus, there is a need for an accessible and easy-to-learn educational medium. This research focuses on designing a mobile learning application to facilitate the learning of tajweed and gharib while incorporating gamification to increase student interest. The design approach uses Player-Centered Design as the framework. The study resulted in a high-fidelity prototype tested through usability testing using cognitive walkthrough methods. The effectiveness evaluation showed a success rate of 94%, efficiency scored 81.13%, and user satisfaction was rated at 77, classified as "Acceptable."